Innovation, asymmetric information and the capital structure of new firms - Jonathan Taglialatela; Andrea Mina (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
The paper focuses on the capital structure of firms in their early years of operation. Through the lens of Pecking Order Theory, we study how the pursuit of innovation influences the reliance of firms on different types of internal and external finance. Panel analyses of data on 7,394 German start-ups show that innovation activities are relevant predictors of the start-ups' revealed preferences for finance, and that the nature of these effects on the type and order of financing sources depends on the degree of information asymmetries specific to research and development activities, human capital endowments, and the market introduction of new products and processes.
Keywords: G32; O16; O30; 330; Innovation; information asymmetries; start-up; pecking order; entrepreneurial finance